HUBUNGAN PENGELOLAAN LIMBAH B3 MEDIS DENGAN KEJADIAN DERMATITIS PADA PEKERJA RONGSOK DI DESA PANGURAGAN KULON KABUPATEN CIREBON - Wanda Aldella; Jaenudin; Putri Mutiara Ramandani (LPPM ITEKES Mahardika, 2019)
Medical hazardous waste management is the process to reducing or eliminating the nature of hazards and toxic. Preliminary study results on scavenger workers which manages medical hazardous waste in Panguragan Kulon Village, Cirebon District were obtained 10 workers, 6 of them (60%), complained of itchy during managing waste, and only 4 workers (40%) who use self protection equipment mask and gloves. The purpose of this research to identify the relationship between medical B3 waste management with incidence of dermatitis on scavengers workers at Panguragan Kulon Village, Cirebon District in 2018. This study using correlation analytic survey, with cross sectional approach. The population is all scavenger workers who manage medical B3 waste in all warehouses at Panguragan Kulon Village, Cirebon District and sampling using a simple random sampling technique. Instrument used in the form of observation sheet. The results Chi-Square is a relationship between the management of medical B3 waste with the incidence of dermatitis in scavenger workers with (p-value = 0,000 < α = 0,05). The recommended implications are increase knowledge and awareness of waste management, especially medical B3 waste and use self-protection equipment and attention to hygiene during work.